2012
DOI: 10.1249/mss.0b013e318228588c
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation Index Immediately after Maximal Exercise in Patients with Type 2 Diabetes Mellitus

Abstract: Patients with T2DM have significantly (and paradoxically) lower postexercise central AIx and greater central AIx reserve, which may be explained by an impaired cardiac functional reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Arterial biomarkers are usually evaluated at rest. However, responses to exercise can reveal physiologic anomalies that are not observable at rest, including vascular alterations 21 , 22 . Furthermore, the integration of cardiac and arterial analyses in exercise can help in understanding the physiologic and pathophysiologic mechanisms of cardiovascular adaptation to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial biomarkers are usually evaluated at rest. However, responses to exercise can reveal physiologic anomalies that are not observable at rest, including vascular alterations 21 , 22 . Furthermore, the integration of cardiac and arterial analyses in exercise can help in understanding the physiologic and pathophysiologic mechanisms of cardiovascular adaptation to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have shown that independent of resting BP, light-moderate exercise hemodynamics can unveil BP abnormalities [16,17] and also predict kidney function in older men [18]. We have also found that patients with T2DM have abnormal responses at higher exercise intensities [19,20]. This study aimed to determine associations between central hemodynamics, including aortic reservoir characteristics, and brain structure in people with and without T2DM, during rest and light-moderate exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Arterial stiffness may play a key role in the occurrence of CV events in patients with T2DM whose HGS is low as we previously reported 9 . Acute handgrip exercises increase AIx and cSBP which is more strongly related to CV than brachial blood pressure in healthy individuals 28 , while AIx decreases after maximal exercise in T2DM patients who usually have impaired cardiac function 29 . The effect of acute exercise on arterial stiffness is different between healthy individuals and patients with T2DM 30 ; therefore, we should also be careful to interpret the association between HGS and AIx in patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%